Small bowel extracts in the inhibition of tumour growth. Issue 1 (January 1975) - Chan, P; Calman, K C; Connor, T A
Abstract : Results presented in this paper confirm earlier experiments which showed that microsomal extract of small bowel, preincubated with tumour cells, resulted in complete inhibition of tumour growth. However, experiments in vitro have shown that this effect is due to direct cytotoxicity of the extract and that (a) it is not specific for the small bowel; (b) it is not specific for tumour cells; and (c) the activity is predominantly in the mitochondrial fraction.